Priority Analysis of Business Unit in S.M.A.R.T Community Portal - Shiddieq, Muhammad Fajar; Saphiranti, Dona (The Indonesian Journal of Business Administration, 2014)
Abstract.PT.DAP plans to launch the S.M.A.R.T Community portal with 8 main features. Portal was launched to increase NetHost user loyalty while increasing average revenues per user. With these features, S.M.A.R.T Community portal will be operated with 6 paid services, each of them has potential advantages as well as different initial capital requirements. The problem, PT.DAP does not have sufficient capital resources to launch simultaneously across business units.Therefore, the research will analyze each business unit based on four sets of tools aimed at determining the best business units that should be prioritized for launch. They are capital budgeting, market analysis, product life cycle, and initial capital requirements. Prioritization is done based on sequences. If after analysis, the business is more profitable by one of analysis method, then it will be prioritized first. If there are results with two or more business units has same or approaching result, then it needs additional tools with subsequent analysis.Data are obtained from surveys that were conducted for research and third-party data. Result of this study is recommendation of business units priority of S.M.A.R.T Community portal. To help complete the next action for PT. DAP, research is also recommending the release schedule for each business unit based on time and circumstances.Keywords: business unit, capital budgeting, market analysis, product life cycle, business unit priority